ECONOMIC AND SOCIAL FACTS OF THE DEVELOPMENT OF THE DIGITAL ECONOMY IN THE REPUBLIC OF UZBEKISTAN - Khatamova Manzura Ochildiyevna (European Science Publishing, 2024)
In order to increase the level of competitiveness of the economy of Uzbekistan, to provide the population with financial, trade and other services that work in the online and offline system, the application of digital technologies in the fields and sectors of the country's economy is scientifically based on the introduction and development of digital technologies in the economy, as well as the problems that hinder their implementation.
Keywords: Uzbekistan, digital economy, gross domestic product, science and technology, digital banking, information and communication technologies, commercial banks, remote banking services, remote services, education.